Innovation Management, from Materiality Assessment to Sustainability Reporting, opening the Social Impact Black Box - Belen Suarez Lopez; Antonio Vargas Alcaide (SocioEconomic Challenges)
When the impossible becomes inevitable. The covid-19 has disrupted increasing the speed of changes in the Industry 4.0, highlighting the need to make a paradigm shift from ego-system to eco-system perspective, challenging organizations and citizens to react from their changemakers role. Two crucial needs arise: firstly, the need to innovate to address the tremendous and complex challenges we face and on the other hand, the need to assess and manage our social impacts. Most organizations should redesign their purpose to focus on measuring, monitoring, and reporting not only in financial terms but also taking into account the non-financial performance, especially in terms of sustainability. Some authors names this time, the era of “stakeholders capitalism”. This paper summarizes the arguments and counterarguments within the scientific, standardization, and business discussion on understanding how organizations could measure their financial, environmental, and social impacts; how to increase the quality of the sustainability reporting, and deliver the most benefit for their stakeholders. The article analyzes the pathway of Innovating, Evaluating and Reporting the Impact, using the materiality assessment as a driver to create value thanks to disruptive technologies as Artificial Intelligence, Blockchain and the Internet of things. The result of the study can be practically valuable for many stakeholders: the Organizations Management and Boards, Chief Innovation Officers and Teams responsible for Sustainability reporting, Auditors assuring the reliability of sustainable reporting, the Scientifics researching on the topic of Innovation, Impact Assessment, and Sustainability; Public Administrations for addressing the economic, social and environmental challenges, and building trust by ensuring transparency and accountability; Investors and other stakeholders interested on understanding long-term value creation and the social and environmental risk assessment to incentivize sustainable growth.